2007
DOI: 10.1177/0883073807304010
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in a Child With Cree Leukodystrophy

Abstract: The authors describe peripheral nerve involvement in a 12-month-old boy with Cree leukodystrophy. Nerve conduction and genetic studies were performed during investigation of his leukodystrophy. Mutation analysis of the eukaryotic initiation factor 2B5 gene detected homozygosity of the R195 mutation, confirming the diagnosis of Cree leukodystrophy. Median and posterior tibial motor nerve conduction study results were normal, but sensory responses in the median nerves were unobtainable bilaterally, in keeping wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was previously thought to occur exclusively in northern Quebec and Manitoba, but a single case has been reported in the Western Canadian province of Saskatchewan. 1,2 The onset is typically between 3 and 9 months of age and affects previously healthy infants, usually following a viral infection or trauma. 3 Previous studies have demonstrated that the imaging characteristics of CLD are similar to those seen in patients with CACH, also known as VWM.…”
mentioning
confidence: 99%
“…It was previously thought to occur exclusively in northern Quebec and Manitoba, but a single case has been reported in the Western Canadian province of Saskatchewan. 1,2 The onset is typically between 3 and 9 months of age and affects previously healthy infants, usually following a viral infection or trauma. 3 Previous studies have demonstrated that the imaging characteristics of CLD are similar to those seen in patients with CACH, also known as VWM.…”
mentioning
confidence: 99%